Biocompatibility of 0,78% tannin of garciniamangostanalinnpericarp extract and 0,2% chlorhexidinegluconateagainst BHK-21 fibroblast cells culture - Monika Werdiningsih; Ira Widjiastuti; Febriastuti Cahyani; Dian Agustin Wahjuningrum (Conservative Dentistry Journal, 2020)
Background.Chlorhexidinegluconate is one of endodontic irrigants potential due to its antibacterial activity. Although it is an effective antibacterial agent, chlorhexidinegluconate cannotdissolve organic substances and necrotic tissue present in the root canal. In addition, same as other chemicals, chlorhexidinegluconate also cause a cytotoxic effect. Tannin extracts of mangosteenpericarp (Garciniamangostana Linn.) demonstrated various biological activities including antibacterial, antioxidant, anticancer and anti-inflammatory. Tannin extracts of mangosteenpericarp can be considered as an alternative endodontic irrigation for dental application.Purpose.The aim of this study was to compare the biocompatibility between 0,78% tannin extracts of mangosteen pericarp and 0,2% chlorhexidinegluconate to BHK-21 fibroblass cell. Method.Tannins obtained from extracts of mangosteenpericarp. Preliminary test was conducted in the biocompatibility of tannin extracts of mangosteenpericarp in various concentrations of the BHK-21 fibroblass. Tannins extracts of mangosteenpericarp was at concentrations of 0,78% less toxic than the other concentrations. Then biocompatibility of 0,78% tannin extracts of mangosteenpericarp compare with 0.2% chlorhexidinegluconate using cytotoxicity test on BHK-21 fibroblass cells with MTT method and observed by ELISA reader. Results.0,78% tannins extracts of  mangosteenpericarp showed good biocompatibility with fibroblass BHK-21 than 0,2% chlorhexidinegluconate. There was a significant differences between the results of treatment with 0,78% tannin extracts of mangosteenpericarp and 0.2% chlorhexidinegluconate. Conclusion. 0,78% tannin extracts of mangosteenpericarp has better biocompatibility than 0,2% chlorhexidinegluconate as an endodontic irrigants.